2019
DOI: 10.1634/theoncologist.2018-0786
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survivors in Metastatic Pancreatic Ductal Adenocarcinoma: A Retrospective and Matched Pair Analysis

Abstract: Background. Metastatic pancreatic ductal adenocarcinoma (mPDAC) is an aggressive malignancy with a median overall survival (OS) of between 8 and 11 months. However, a significant number of patients experience a longer survival, more than 18 months. The aim of this study was to describe the "long-term survivor" population and to evaluate clinical and pathological factors that might affect survival. Materials and Methods. All patients with mPDAC diagnosed in the Centre Leon Bérard (Lyon, France) between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…According to the eighth edition of the pancreatic cancer staging published by the American Joint Committee on Cancer (AJCC), pancreatic cancer with distant metastases are defined as M1 11 . Additionally, only a limited number of studies have investigated the occurrence rate and prognostic value of different metastatic patterns in pancreatic cancer 12 - 14 . Furthermore, almost no guidelines have taken the number and site of metastases into consideration for the treatment of metastatic pancreatic cancer (MPC).…”
Section: Introductionmentioning
confidence: 99%
“…According to the eighth edition of the pancreatic cancer staging published by the American Joint Committee on Cancer (AJCC), pancreatic cancer with distant metastases are defined as M1 11 . Additionally, only a limited number of studies have investigated the occurrence rate and prognostic value of different metastatic patterns in pancreatic cancer 12 - 14 . Furthermore, almost no guidelines have taken the number and site of metastases into consideration for the treatment of metastatic pancreatic cancer (MPC).…”
Section: Introductionmentioning
confidence: 99%
“…NLR, which is a parameter of systemic inflammatory and immune reactions, may play an important role in the progression of solid tumors ( 38 ), including PDAC ( 39 , 40 ). Recent studies have reported that elevated preoperative NLR is a significant marker for predicting malignant IPMNs ( 14 , 25 , 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation has been associated with the initiation, development, and progression of many cancers. In pancreatic cancer, the elevation of NLR and PLR are independent prognostic factors predicting a poor outcome ( 16 18 ), and LMR predicts a better outcome ( 19 , 20 ). Consistently, these prognostic factors were significantly associated with overall survival in the univariate analysis in the present study.…”
Section: Discussionmentioning
confidence: 99%